Oral aspirin or low dose of intravenous lysine acetylsalicylate in ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 7 (July 2021) - Ferlini, Marco; Leonardi, Sergio; Mandurino Mirizzi, Alessandro; Montalto, Claudio; Crimi, Gabriele; Repetto, Alessandra; Marinoni, Barbara; Somaschini, Alberto; Ferrario, Maurizio; Klersy, Catherine; Oltrona Visconti, Luigi
Abstract : Aim: To compare the pharmacodynamic effect of an oral loading dose of 'noncoated' ASA 300 mg vs. an intravenous bolus injection of lysine acetylsalicylate 150 mg in patients with STEMI undergoing pPCI. Methods: This was a prospective single-center, open label, pharmacodynamic study, including nonconsecutive patients presenting at our catheterization laboratory with STEMI undergoing pPCI and not receiving ASA within the previous 7 days. Pharmacodynamic analyses were performed at five time points: baseline, and 1, 2, 4 and 12 h after the loading dose, and measured as ASA reaction units (ARU) by the Verify Now System. An ARU more than 550 was considered as nonresponsiveness to study drugs. The primary end point was the different rate of patients with ARU more than 550 at 2 h after the loading dose of oral vs. intravenous ASA. Secondary end points included the comparison of ARU more than 550 at the other time points and the comparison of continuous ARU at each time point. Results: The study was planned with a sample size of 68 patients, but it was prematurely stopped due to slow enrollment after the inclusion of 23 patients, 12 randomized to oral ASA and 11 to intravenous lysine acetylsalicylate. At 2 h the rate of patients with ARU more than 550 was numerically but not significantly higher in patients receiving oral ASA as compared with intravenous lysine acetylsalicylate (33 vs. 14.2%; Δ −0.19, 95% confidence interval −0.59–0.21, P  = 0.58). The difference over time was NS ( P  = 0.98), though the prevalence of ARU more than 550 was higher at the other time points. Both routes of administration reduced ARU values over time, though with no overall significant difference between profiles ( P overall = 0.48). Conclusion: In patients with STEMI undergoing pPCI the rate of nonresponsiveness to ASA was not different comparing an oral 'noncoated' loading dose of ASA with an intravenous bolus injection of lysine acetylsalicylate. However, as patient enrollment was prematurely terminated, this study is underpowered to draw a definite conclusion. Abstract : Supplemental Digital Content is available in the text